2016
DOI: 10.5851/kosfa.2016.36.6.752
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for Predicting the Growth Probability of Staphylococcus aureus in Combinations of NaCl and NaNO2under Aerobic or Evacuated Storage Conditions

Abstract: The objective of this study was to describe the growth patterns of Staphylococcus aureus in combinations of NaCl and NaNO 2, using a probabilistic model. A mixture of S. aureus strains (NCCP10826, ATCC13565, ATCC14458, ATCC23235, and ATCC27664) was inoculated into nutrient broth plus NaCl (0, 0.25, 0.5, 0.75, 1, 1.25, 1.5, and 1.75%) and NaNO 0,15,30, 45, 60, 75, 90, 105, and 120 ppm). The samples were then incubated at 4, 7, 10, 12 and 15°C for up to 60 d under aerobic or vacuum conditions. Growth responses [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This result suggests that S. aureus can survive in beef jerky even if A W is less than 0.850. Additionally, Lee et al (2016) indicated that S. aureus did not grow under vacuum conditions. Hence, we developed predictive models using the seasoned beef jerky products as a model product under aerobic conditions to predict the most severe case of S. aureus growth.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that S. aureus can survive in beef jerky even if A W is less than 0.850. Additionally, Lee et al (2016) indicated that S. aureus did not grow under vacuum conditions. Hence, we developed predictive models using the seasoned beef jerky products as a model product under aerobic conditions to predict the most severe case of S. aureus growth.…”
Section: Resultsmentioning
confidence: 99%
“…However, MRS medium supplemented with nitrate was used as a negative control and did not exhibit antimicrobial activity. Nitrite is also effective against other foodborne pathogens including Bacillus cereus, Enterococcus faecalis, Listeria monocytogenes, E. coli O157:H7, and Staphylococcus aureus in meat products (Buchanan et al, 1989;Harrison et al, 1998;Lee et al, 2016;Redondo, 2011;SAMESHIMA et al, 1997) Nitrate reduction and nitrite production (Gotterup et al, 2007). Marked, highly effective NaNO2 production by the most efficient strain S. hominis subsp.…”
Section: Antimicrobial Activitymentioning
confidence: 99%